Nitrogen and energy balance in lactating and non lactating goats which obtained additional ration ofo cooked cassava and urea - Nathan Katipana; Sastradipraja D. (Hemera Zoa, 1991)
This research used 27 of Etawah crossbred goats which consisted of 18 lactating and 9 non lactating. The ration used were three kinds namely ration A consisted only of fresh elephant grass added with uncooked cassava and urea, and ration C consisted of fresh elephant grass added with cooked cassava and urea.Nitrogen and energy retention of lactating and non lactating goats as the results of the applications of ration C and ration B are high significantly (p < 05) superior than ration A. Nitrogen andn energy retention as the result of the application of ration C are not signiificantly from that of ration B.Milk production due to the applications of rations C and B are higher than ration A (p < .05). Application of ration C increases the content of solids, solid non fat, protein and the spesific gravity of the milk. It also increases the production of  fat, solids, solid non fat and protein of the milk. It seems that the contents of solid and solid non fat are determined by the value of protein. It is concluded that addition of cooked cassava and urea can improve the utilization of foodstuff protein.